2020
DOI: 10.1021/acs.langmuir.0c00523
|View full text |Cite
|
Sign up to set email alerts
|

Macroscale Light-Controlled Lubrication Enabled by Introducing Diarylethene Molecules in a Nanoconfinement

Abstract: Reversible friction regulation is of long-standing great interest in the fields of both industry and scientific research, so some materials and theories have been developed aiming to solve this problem. Light-sensitive materials are promising because of the easy controllable switching of the properties and structures. Here, a reversible light-controlled macrolubrication was realized by regulating the performance of nanoscale light-sensitive molecules adsorbed on contact surfaces. In this work, symmetric diaryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…5(d). The COF change ranges were 20%-100% in other works of light-induced friction [5,55,56]. Further studies of light-controlled friction fatigue tests showed that the friction regulations underwent reversible transformation under UV and NIR light, as shown in Fig.…”
Section: Friction Regulation By Photosensitive Rheological Fluidsmentioning
confidence: 66%
See 1 more Smart Citation
“…5(d). The COF change ranges were 20%-100% in other works of light-induced friction [5,55,56]. Further studies of light-controlled friction fatigue tests showed that the friction regulations underwent reversible transformation under UV and NIR light, as shown in Fig.…”
Section: Friction Regulation By Photosensitive Rheological Fluidsmentioning
confidence: 66%
“…The viscosity of fluids is closely tied to industrial production and daily life, such as in navigation [1,2], pipe flows [3], mechanical lubricants [4][5][6][7][8][9][10][11], water conservancy, and biorheology [12,13]. In particular, with the development of intelligent fluids such as electrorheological fluids [14,15], magnetorheological fluids [16][17][18][19][20], pH-sensitive fluids [21], photorheological fluids [22][23][24], and other stimuli-responsive fluids [25,26], these intelligent fluids are attracting extensive attention as smart fluid dampers for vehicle [27,28], oil and gas pipeline transportation [29], in wafer surface polishing [30,31], and friction regulation [5,[32][33][34][35][36]. However, some intelligent fluids have disadvantages, such as in electrochemical corrosion in electrorheological fluids.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some studies on the tribological properties of the self-assembled organic molecule layers ( Nalluri et al, 2011 ; Shi et al, 2018 ), while the studies on the tribological properties of the photo-regulated molecular layers have been reported rarely ( Pace et al, 2007 ; Tang et al, 2020 ). For the self-assembly layers of the NN4A and NN2A molecules, we had investigated the tribological lateral forces using AFM at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…In general, external field regulation is the way that people usually choose, such as light stimulation, electric field, heat, chemicals, etc. ( Zhang et al, 2012 ; Yokoyama et al, 2014 ; Cai et al, 2017 ; Cao et al, 2018 ; Meng et al, 2020 ; Tang et al, 2020 ). Among all possibilities, light is probably utilized to realize intelligent control of photochromic self-assembly due to its remote control, non-invasive, and cleaning properties.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, photorheology is a cutting-edge field where active control of viscosity can be achieved by light . Recently, active control of lubrication by UV–visible illumination of a ball-on-disc tribological system has been reported . Also, the direction of the motion of 3,3′-dimethylazobenzene crystals on a glass surface could be actively controlled by the position of the light sources .…”
Section: Introductionmentioning
confidence: 99%